Pengaruh Disiplin Kerja Dan Komunikasi Terhadap Kinerja Karyawan Unit Teleoperation PT. Bfi Finance Indonesia Tbk Kota Tangerang Selatan - Arsyka Nabilla Aisya; Dewi Sartika (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the significant influence between Work Discipline and Communication both partially and simultaneously on Employee Performance at the Teleoperation unit of PT BFI Finance Indonesia Tbk. The research method used is a quantitative descriptive method. The population used is employees at the Teleoperation unit of PT BFI Finance Indonesia Tbk as many as 99 people. The sample used was 99 people. The sampling technique is the saturated sample technique. The data analysis test used is the Validity Test, Reliability Test, Normality Test, Heteroscedasticity Test, Autocorrelation Test, Correlation Coefficient Test, Determination Coefficient Test R, Simple and Multiple Regression Analysis Test, Hypothesis t Test and F Test (Simultaneous). The results of this study are work discipline has a significant effect on employee performance as indicated by the results of the hypothesis test obtained t count > t table or (12.535 > 1.661). Communication has a significant effect on employee performance as indicated by the results of the hypothesis test obtained by t count > t table or (13.667 > 1.661). Work Discipline and Communication have a significant effect on employee performance as indicated by the results of the hypothesis test obtained by F count > F table or (99.228 > 2.700).